Measurement of the factors affecting the quality of life in the informal settlements areas of Tabriz Metropolis - Nazli pakru; Rasoul Darskhan (تحقیقات کاربردی علوم جغرافیایی)
Rapid urbanization causes the number of problems for citizens and urban managers, which noted the need to adopt strategies and approaches to improve the condition. In the meantime, the concept of quality of life was developed to assess the condition in cities. The quality of life as a multidimensional concept in the economic, social, physical, and other dimensions has been discussed and utilized at various levels and scales. In this research, with the aim of measuring the quality of life in informal settlements of Tabriz, survey method has been used for this purpose. It can be said that the mental attitude of quality of life dominates this research, which Satisfaction and mental opinion of the residents are the basis of work. One-sample T-test and path analysis were used to analyze the data. The results indicate that the average of all dimensions of quality of life is lower than the average, and the only socio-cultural factor is higher than the average. Also, the average total quality of life is 2.82, lower than the average, which reflects the poor quality of life in these neighborhoods. Based on path analysis, the economic dimension with 0.685 has the greatest impact on the quality of life in these neighborhoods. It can be said that any planning for these neighborhoods will be done taking into account different dimensions, in order to be effective.